PELAKSANAAN MUSYAWARAH PERENCANAAN PEMBANGUNAN DESA (MUSRENBANGDES) DI DESA CINTA DAMAI KECAMATAN TAPUNG HILIR TAHUN 2022 - Saputra, Danang Wijaya; Susanto, Agus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research is based on the problem of a lack of active community participation in implementing the musrenbang of Cinta Damai Village, Tapung Hilir District, as well as the lack of application of the principles of implementing the musrenbangdes in accordance with the Decree of the Minister of Home Affairs No.050- 187/Kep/Bangda/2007. This research also explains the factors inhibiting the implementation of musrenbang in Cinta Damai Village. Then, this research uses a qualitative descriptive research approach, where the type of data used is primary data from key informants and secondary data that is relevant to the research context. Data collection techniques used include interview techniques and documentation. Next, the data analysis technique uses qualitative descriptive analysis techniques to answer the research questions asked. The results of this research show that the lack of active participation in the implementation of the musrenbangdes in Cinta Damai Village is influenced by several factors, from socio-economics, egocentric nature, knowledge, skills, attitudes and political views. This caused the implementation of the musrenbang in Cinta Damai Village to not run as well as it should Keywords: Musrenbangdes, Implementation, Planning